2009
DOI: 10.1073/pnas.0810790106
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen promotes the survival and pulmonary metastasis of tuberin-null cells

Abstract: Lymphangioleiomyomatosis (LAM) is an often fatal disease primarily affecting young women in which tuberin (TSC2)-null cells metastasize to the lungs. The mechanisms underlying the striking female predominance of LAM are unknown. We report here that 17-␤-estradiol (E2) causes a 3-to 5-fold increase in pulmonary metastases in male and female mice, respectively, and a striking increase in circulating tumor cells in mice bearing tuberin-null xenograft tumors. E 2-induced metastasis is associated with activation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
204
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 157 publications
(215 citation statements)
references
References 37 publications
10
204
0
1
Order By: Relevance
“…E 2 , upon binding to its estrogen receptor (ER), has been reported to regulate transcriptiondependent and -independent signaling events (14). Thus, in addition to its ability to promote changes in gene expression (10,(15)(16)(17)(18), E 2 can induce the activation of signaling proteins such as Src, Akt, and ERK-MAP kinase (14). The importance of ERK-MAP kinase in LAM was suggested by a recent report showing that E 2 promoted the MEK-dependent invasion of cells derived from Eker rat uterine leiomyoma (ELT3 cells) into the lungs of ovariectomized mice (18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…E 2 , upon binding to its estrogen receptor (ER), has been reported to regulate transcriptiondependent and -independent signaling events (14). Thus, in addition to its ability to promote changes in gene expression (10,(15)(16)(17)(18), E 2 can induce the activation of signaling proteins such as Src, Akt, and ERK-MAP kinase (14). The importance of ERK-MAP kinase in LAM was suggested by a recent report showing that E 2 promoted the MEK-dependent invasion of cells derived from Eker rat uterine leiomyoma (ELT3 cells) into the lungs of ovariectomized mice (18).…”
mentioning
confidence: 99%
“…Thus, in addition to its ability to promote changes in gene expression (10,(15)(16)(17)(18), E 2 can induce the activation of signaling proteins such as Src, Akt, and ERK-MAP kinase (14). The importance of ERK-MAP kinase in LAM was suggested by a recent report showing that E 2 promoted the MEK-dependent invasion of cells derived from Eker rat uterine leiomyoma (ELT3 cells) into the lungs of ovariectomized mice (18). However, the molecular basis for E 2 -dependent ERK contribution to the enhanced invasive phenotype in the presence of constitutively activated mTORC1 was not defined, and whether E 2 promoted a similar response in patient-derived cells remained to be determined.…”
mentioning
confidence: 99%
“…[136][137][138][139] Separate studies suggested that prolactin stimulates mTOR, and modifies STAT1 activity in mTOR-dependent fashion. 140,141 Further studies are required to better understand how mTORCs interact with androgen or estrogen signaling pathways.…”
Section: Other Emerging Mtor Targets In Lammentioning
confidence: 99%
“…Estrogen also enhances the number of circulating tumor cells and the survival of intravenously injected ELT3 -cells. 38 In vitro, estrogen-treated ELT3 cells exhibit induced resistance to anoikis and decreased levels of caspase-3 cleavage. Using the Xenogen bioluminescent imaging (Caliper Life Sciences, Hopkinton, MA), estrogen treatment causes a twofold increase in lung colonization of intravenously injected ELT3-luciferase cells at 3 h, and a five-fold increase at 24 h (Fig.…”
Section: Estrogen Promotes the Survival And Metastasis Of Tsc2-null Cmentioning
confidence: 99%